2021
DOI: 10.3390/app112411640
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chemical Activating Agent on the Properties of Activated Carbon from Sago Waste

Abstract: The effect of chemical activators on the properties of activated carbon from sago waste was conducted in this study by using ZnCl2, H3PO4, KOH, and KMnO4 chemical solutions. The carbonized sago waste was added to each chemical solution, boiled at 85 °C for 4 h, and heated at 600 °C for 3 h. The porosity, microstructural, proximate, and surface chemistry analyses were carried out using nitrogen adsorption with employing the Brunauer Emmett Teller (BET) method and the Barret-Joyner-Halenda (BJH) calculation, sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The samples were later dried in an oven at a temperature of 110℃ for 2 h to get the activated carbon product. Detailed procedures are available in the previous report [10], and the product was donated as total activated carbon.…”
Section: Activated Carbon Fabricationmentioning
confidence: 99%
See 2 more Smart Citations
“…The samples were later dried in an oven at a temperature of 110℃ for 2 h to get the activated carbon product. Detailed procedures are available in the previous report [10], and the product was donated as total activated carbon.…”
Section: Activated Carbon Fabricationmentioning
confidence: 99%
“…The carbon material was prepared using a ZnCl2 activator reagent, with a surface area of more than 500 m 2 •g -1 and a relatively high carbon content at 40%. A surface chemistry study also found that the activated carbon also consists of phenol and carboxylate groups [4,10].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…23 The AB prepared with ZnCl 2 acid had a high specific surface area of 546.61 m 2 g −1 . 24 The acid modification process improves the amount of oxygen-containing functional groups in biochar, 25 especially H 3 PO 4 modification that could increase the number of –COOH and –OH groups on the surface of biochar. 26 The H 3 PO 4 modification was propitious to form disordered carbon at the fixed pyrolysis temperature, which implied a low degree of graphitization.…”
Section: Introductionmentioning
confidence: 99%
“…Fundamentally, the porous and adsorption properties of chemically prepared AC depend on the pyrolysis conditions and the type of precursors (preferably high-carbon, low-ash, high-availability and low-cost precursors) 2 and the activators used. Often chemical activation contributes to the porous structure and chemical properties of AC 21 and many chemical activators, such as ZnCl 2 21 , KMnO 4 22 , H 3 PO 4 23 , KOH and K 2 CO 3 24 , have been used in the preparation of AC.…”
Section: Introductionmentioning
confidence: 99%